Simbol Religius pada Rumah Gadang Abai Sangir, Solok Selatan - Dedy Gusman (Jurnal Elektronik WACANA ETNIK, 2011)
This research describes religious symbols at rumah gadang Abai Sangir Solok Selatan. The symbols lay on walls, stairs, doors, and windows. Using the descriptive qualitative method and Paul Ricoer theory, the research shows that the society put on their belief on those symbols. How they live as person and society described on the symbols.